Valuation and vulnerability. An analysis of the reception of two illness narratives in the contemporary Swedish literary landscape - Lenemark, Christian (Folia Scandinavica Posnaniensia, 2024)
The proliferation of autobiographical accounts of illness, or autopathographies, has attracted considerable scholarly interest. Nevertheless, a notable gap remains in our understanding of how these narratives are received and evaluated. This article addresses this gap by examining the dynamics of value negotiation surrounding two autobiographical illness narratives in Sweden: Kristina Sandberg’s En ensam plats (A Lonely Place, 2021) and Sara Meidell’s Ut ur min kropp (Out of My Body, 2022). Theoretically, the article is grounded in a constructivist framework of value. In addition to exploring how Sandberg and Meidell address the value question in their illness narratives, it presents a detailed analysis of reviews and debate articles to uncover the underlying values expressed in the reception of these narratives. The analysis reveals that the value discussions center on aesthetic, emotional, social, and ethical dimensions, reflecting broader cultural debates about illness and its representation. While Sandberg’s narrative raises questions about the portrayal of illness experiences, Meidell’s narrative provokes discussions about its potential impact on readers. In sum, this article highlights the need for a comprehensive understanding of value creation and negotiation pertaining to illness narratives.